2019
DOI: 10.1057/s41288-019-00151-9
|View full text |Cite
|
Sign up to set email alerts
|

Livestock insurance, moral hazard, and farmers’ decisions: a field experiment among hog farms in China

Abstract: Moral hazard is believed to influence farmers' production decisions and undermine the effectiveness of insurance programmes. In this study, a 2-year field experiment is conducted among hog farms in four townships in China to investigate the effects of a government-subsidised insurance programme on farmers' decisions and production outcomes. A joint estimation procedure combining propensity score matching with difference-in-difference is deployed to control for selection bias caused by observable and unobservab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…A plausible explanation is that tourism in China is still a comparatively luxury experience for citizens and that they attach a high value to their travel time at tourism destinations. Thus, there are potential differences in the role time plays in the decision-making process (Rao, 2018;Rao et al, 2019;Rao & Zhang, 2020). It is suggested that this phenomenon warrants further research in the hospitality and tourism fields and more studies in other contexts to better understand travellers' consumer behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…A plausible explanation is that tourism in China is still a comparatively luxury experience for citizens and that they attach a high value to their travel time at tourism destinations. Thus, there are potential differences in the role time plays in the decision-making process (Rao, 2018;Rao et al, 2019;Rao & Zhang, 2020). It is suggested that this phenomenon warrants further research in the hospitality and tourism fields and more studies in other contexts to better understand travellers' consumer behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Our experiment includes members from a specific group that had actually purchased hog insurance, and another that did not. We surmise that farmers with prior exposure to hog insurance purchases would reveal preferences that are different 2 The context as well as the natural experiment in our study are the same as in Rao and Zhang (2020) but the focus of these two studies is different. Specifically, Rao and Zhang mainly examined the impact of livestock insurance on farmers' hazardous actions as well as production decisions by exploiting a twoyear natural experiment.…”
Section: Introductionmentioning
confidence: 98%
“…Ensuring sufficient pork supply remains a top concern of the Chinese government (Chen and Wang 2013). China supplied more than 708 million hogs in 2015, accounting for almost half of global production (Rao and Zhang 2020). A salient feature of China's hog production is its large number of spatially scattered, small-sized hog farms 1 that rely on the intensive use of labour and outdated technologies (Zhang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations